Caspase‐6‐cleaved tau is relevant in Alzheimer's disease but not in 4‐repeat tauopathies: Diagnostic and therapeutic implications. (December 2021) - Piergies, Antonia M. H.; Theofilas, Panos; Li, Song; Petersen, Cathrine; Ehrenberg, Alexander J.; Eser, Rana April; Chin, Brian; Yang, Teddy; Khan, Shireen; Ng, Raymond; Spina, Salvatore; Seeley, William W.; et al.
Abstract: Background: Tau truncation by active caspase‐6 facilitates tau pathogenesis by producing toxic fragments prone to self‐aggregation. We previously demonstrated that neuronal active caspase‐6 co‐occurs with phosphorylated tau (p‐tau) during the earliest stages of Alzheimer's disease (AD) and that the percentage of neurons positive for both active caspase‐6 and p‐tau increases as the disease progresses. Although caspase‐6‐mediated cleavage of tau appears to be a key contributor to tau pathology, questions concerning the relationship between caspase‐6 activation, tau cleavage, and the formation of p‐tau aggregates remain. Methods: We developed novel neoepitope antibodies against tau truncated by caspase‐6, performed 5‐plex immunofluorescence on tissue microarrays—sampled from the middle frontal gyrus (MFG) and the inferior temporal gyrus (ITG)—and quantified neuronal and glial positivity for active caspase‐6, tau truncated at D402 and D13 (tr‐tau; C‐ and N‐terminal, respectively), and tau phosphorylated at Ser202 (p‐tau; CP13) in AD, argyrophilic grain disease (AGD), corticobasal degeneration (CBD), Pick's disease (PiD), progressive supranuclear palsy (PSP), and healthy aging controls. Results: Percentages of neurons positive for p‐tau were as to be expected in all 17 cases. AD showed the highest burden of neuronal positivity for active caspase‐6, followed by PiD (Figure 1, Table 1). Mean percentages of neurons positive for D402 and D13 were markedly higher (1.80 to 236x) in AD and PiD relative to the 4‐repeat tauopathies tested (Figure 1, Table 1). Surprisingly, in AD, only ∼44.36% of these neurons showed p‐tau positivity (Figure 2). Regarding glial positivity, active caspase‐6 and tr‐tau were present in PSP but scarce in CBD (Figure 3, Table 2). Conclusions: (1) Caspase‐6 activation and cleavage of tau is more prominent in AD and, to a lesser extent, PiD. Caspase‐6 modulation could be a promising therapeutic for AD, and possibly PiD, but not 4‐repeat tauopathies. (2) In AD, there is a substantial number of neurons with tr‐tau inclusions that lack p‐tau, which suggests that biofluid biomarkers of tr‐tau (specifically at N‐terminal sites) would allow for better detection of AD and differentiation of AD from 4‐repeat tauopathies.